Exergo-environmental analysis of an indirect forced convection solar dryer for drying bitter gourd slices. (February 2020) - Vijayan, S.; Arjunan, T.V.; Kumar, Anil
Abstract: In this study, a low cost indirect forced convection solar dryer integrated with porous bed sensible heat storage medium has been developed and studied under the climatic conditions of Coimbatore for drying bitter gourd slices. The experimental setup consists of a solar collector with 2 m 2 area, drying chamber and a centrifugal blower to force the air. The main objective of the study is to investigate the effect of mass flow rate of air on the exegetic and pickup efficiencies of the solar drying system for drying bitter gourd slices. The results indicate that the mass of the bitter gourd slices was reduced from 4000 to 723 g in 7 h at the mass flow rate of air 0.0636 kg/s in solar drying system. The average exergy efficiency values vary from 28.74% to 40.67% for the mass flow rates of air from 0.0141 to 0.0872 kg/s respectively. The average pickup efficiency of the drying air varied from 54.29% to 17.18% for various mass flow rates of air and it decreases with increase in mass flow rate of air. The effective moisture diffusivity of bitter gourd slices was observed from 8.6293 × 10 −10 to 12.9585 × 10 −10 m 2 /s, whereas for open sun drying it gives the lowest value of 0.9568 × 10 −10 m 2 /s. Environmental impact analysis indicated that the energy payback time for the indirect solar dryer is found to be 2.21 years only. The CO2 mitigation and earned carbon credit values for the developed system are 33.52 tons and INR 10894 to 43576 for the expected lifetime of 35 years. Impact analysis shows that the solar dryer is a suitable solution for preserving the agricultural products with environmental sustainability. Highlights: Effect of mass flow rate of air on exergy and pickup efficiencies were studied. The average pickup efficiency of the dryer varies from 17.12 to 54.29%. Exergy efficiency varies from 28.27 to 40.68% for 0.0141–0.0872 kg/s. Deff of bitter gourd slices vary from 8.6293 × 10 −10 to 12.9585 × 10 −10 m 2 /s. CO2 mitigation & earned carbon credit values are 33.52 tons and INR 10894 to 43576.